ANALYSIS OF COOPERATION BETWEEN CLASS XII IIS 2 STUDENTS IN MUHAMMADIYAH 1 PONTIANAK HIGH SCHOOL - Isman, Heryana M (Jurnal Pendidikan Sosiologi dan Humaniora, 2019)
This study aimed to describe the spontaneous cooperation, contracts, and traditional inter IIS 2 class XII students at SMA Muhammadiyah 1 Pontianak. The method used is qualitative approach. The results showed that spontaneous cooperation among students have been executed better, but not perfect because there are students who are less well spontaneous cooperation. Besides the cooperation contract between the students has been reached with the good, it is characterized by cooperation between students when carrying picket class and their prayer materials to other students. While the traditional cooperation between students has also been going well between them visible influence each other as well as snacks at canteen, there is always one of the students who invited more friends for snacks at canteen together, and call it received good response by other friends to be said that these interactions may affect the behavior of other individuals by creating social relations among them